Turkish validity and reliability of the Internalized AIDS-Related Stigma Scale - ARDIÇ, ELİF (WILEY, 2021)
Purpose This study was conducted methodologically to adapt the Internalized AIDS-Related Stigma Scale (IA-RSS) to Turkish society. Design and Methods The universe of the study consisted of 250 people who were treated in the infectious diseases outpatient clinic. A total of 60 individuals living with human immunodeficiency virus (HIV) composed the sample. The Individual Information Form and IA-RSS were used for data collection. Findings All the statistical procedures performed in the validity and reliability stages of the study show that the scale is a valid, reliable measurement tool for the Turkish culture. Practice Implications The Turkish version of the IA-RSS was determined as a valid and reliable screening tool that measures internal stigmatization in living with HIV.
Keywords: HIV(+); AIDS; internalized stigma; validity and reliability; HIV-RELATED STIGMA; MEDICATION ADHERENCE; DEPRESSIVE SYMPTOMS; LONELINESS; HIV/AIDS; QUALITY; THERAPY; MEN; SEX